Copper niobate nanowires boosted by a N, S co-doped carbon coating for superior lithium storage. Issue 32 (29th July 2021) - Cai, Xinhao; Yan, Huihui; Yang, Zhengwei; Li, Wenru; Yu, Haoxiang; Yan, Lei; Zhang, Liyuan; Shui, Miao; Cui, Yanhua; Shu, Jie
Abstract : N, S co-doped carbon layer boosts the kinetic properties of Cu2 Nb34 O87 nanowires as anode host for lithium-ion batteries. Abstract : With the development of electric vehicles, more and more attention has been paid to the kinetic performance of batteries, which is related to rapid charge/discharge and safety issues. To improve this aspect, Cu2 Nb34 O87 nanowires covered by nitrogen and sulfur co-doped carbon (Cu2 Nb34 O87 /NSC nanowires) are prepared by electrospinning combined with surface coating. As-prepared Cu2 Nb34 O87 /NSC nanowires present a high ion diffusion coefficient and electronic conductivity, showing good a kinetic performance. Specifically, they deliver a splendid capacity of 311.2 mA h g −1 at 1 C and a superior cycling stability with a capacity fading of 0.031% per cycle upon 1000 cycles. At the same time, the electrochemical and structural reversibility is fully discussed and demonstrated by ex situ XRD, ex situ SEM and ex situ XPS based on the redox couples of Cu 2+ /Cu +, Nb 5+ /Nb 4+, and Nb 4+ /Nb 3+ . Contributing to peculiar physico-chemical properties, Cu2 Nb34 O87 /NSC nanowires are expected to be a candidate material for the anode in lithium-ion batteries.